MENINGKATKAN MORALITAS REMAJA MELALUI DUKUNGAN SOSIAL - Budiyono, Alief (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2010)
Young people are in transition from childhood towards adulthood, require special attention. In adolescence,they begin to search for identity. This period is often referred to as the rise of personality when his interest is more directed to theirown personal development. To instill morals in adolescents, it is indispensable support from various sources, be it family,society, peers, and school environment. With positive support from everyone, teens are expected to have good morals.However, if all the poles are not able to give warm support to the teenager, then teenagers will be experiencing moral crisis.